Contribution of End Grain of Wood in Vacuum Drying - Kumar, Shailendra; Topare, Rushikesh R. (Indian Forester, 2019)
Wood specimen of Melia composita were dried in a vacuum press dryer under two initial moisture contents (IMC) i.e., above and below fibre saturation point (FSP). In order to understand the effect of end grain on vacuum drying, half of the wood specimens were end sealed and remaining half were left with unsealed ends. Two drying runs i.e. with initial moisture contents above and below fibre saturation point, with both types of wood specimen (end sealed and unsealed ends) were conducted. The contribution of end grains in wood drying is insignificant when IMC is below FSP. The drying rates were more than 3-4 times higher for specimens with high IMC i.e. above FSP.